Dynamic oneness : the significance and flexibility of Paul's one-God language - Nicholson, Suzanne (James Clarke & Co, 2011)
The apostle Paul affirms in several places that there is only one God. Yet in the same letters Paul also gives praise to the Lord Jesus Christ, often using language similar to his descriptions of God. How can this self-avowed Hebrew of Hebrews reconcile these ideas? This book explores the strongest one-God statements in Paul's undisputed letters and asks how Paul's Jewish monotheistic understanding informs his overall argument. These three texts - 1 Corinthians 8:6, Galatians 3:20, and Romans 3:30 - occur in very different contexts and address different issues. By looking at the historical, cu.